Anti-Human Herpesvirus 6 A/B Antibodies Titers Correlate With Multiple Sclerosis-Associated Retrovirus Envelope Expression - Pérez-Pérez, Silvia; Domínguez-Mozo, María I.; García-Martínez, M. Ángel; García-Frontini, M. Celeste; Villarrubia, Noelia; Costa-Frossard, Lucienne; Villar, Luisa M.; Arroyo, Rafael; Álvarez-Lafuente, Roberto (Frontiers in Immunology, 2021)
Human endogenous retrovirus W family envelope proteins (pHERV-W ENV/syncytin-1) have been repeatedly associated with multiple sclerosis (MS). Here, we have focused on the study of pHERV-W ENV/syncytin-1 expression levels in MS patients (relapsing and progressive forms) and in healthy donors (HD) and on exploring their possible relationship with Epstein-Barr virus (EBV) and human herpesvirus-6A/B (HHV-6A/B). We included blood samples from 101 MS patients and 37 HD to analyze antiviral antibody titers by ELISA and pHERV-W ENV/syncytin-1 expression levels by flow cytometry as well as by qPCR. Patients with relapsing MS forms showed significantly higher pHERV-W ENV/syncytin-1 protein and gene expression levels than HD. Progressive MS patients also showed significantly higher protein and gene expression levels than both HD and relapsing MS patients. Regarding antiviral antibodies titers, anti-HHV-6A/B IgM levels were positively correlated with pHERV-W ENV/syncytin-1 protein expression levels in patients with relapsing MS, while in the progressive forms patients this correlation was found with anti-HHVA/B IgG levels. Therefore, pHERV-W ENV could be involved in MS pathogenesis, playing a role in relapsing and progressive forms. Besides, anti-HHV-6A/B antibodies positively correlated with pHERV-W ENV expression. Further studies are needed to better understand this possible relationship.